Optimized design of daylight redirection microstructures combined with planar micro structured light sources for high efficient room lighting integrated in building façades. (September 2017) - Jakubowsky, Michael; Neyer, Andreas
Abstract: In the course of claiming more energy efficient buildings it is necessary to reduce the amount of artificial lighting. With the aim of realizing a very thin system integrated into building façades microstructures for the redirection of daylight are developed. In order to achieve sufficient room lighting at night or other situations of less sunshine, this daylighting system is coupled to a system for artificial lighting consisting of a microstructured light guide plate. This system transforms LED point light sources to a planar light source, which lights the room ceiling. The micro structures, its functionality and application are explained.